A Decomposition Method with Redistributed Subroutine for Constrained Nonconvex Optimization. (26th February 2013) - Lu, Yuan; Wang, Wei; Pang, Li-Ping; Li, Dan
Abstract : A class of constrained nonsmooth nonconvex optimization problems, that is, piecewise C 2 objectives with smooth inequality constraints are discussed in this paper. Based on the 𝒱 𝒰 -theory, a superlinear convergent 𝒱 𝒰 -algorithm, which uses a nonconvex redistributed proximal bundle subroutine, is designed to solve these optimization problems. An illustrative example is given to show how this convergent method works on a Second-Order Cone programming problem.